2006
DOI: 10.1590/s0100-29452006000200032
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência e crescimento de mudas de pessegueiro interenxertadas

Abstract: Os experimentos foram realizados no viveiro da Embrapa Transferência de Tecnologia em Canoinhas SC, no período de dezembro de 2003 a julho de 2005. Estudou-se o efeito de interenxertos, na produção de mudas de pessegueiro. Os tratamentos foram: combinação de dois porta-enxertos ('Okinawa' e 'Capdeboscq'), quatro interenxertos (ameixeira 'Reubennel' e 'Irati', um umezeiro e uma cerejeira 'Capulin') e duas copas ('Coral' e 'Chimarrita'). O delineamento experimental inicial foi inteiramente ao acaso, com 20 trata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…This technique aims to reduce the vigor of plants, increase yield efficiency, and improve fruit quality. These effects have already been verified in several fruit species, such as peach (Rufato et al, 2006;Scarpare Filho et al, 2000;Telles, Biasi, Mindello Neto, & Peters, 2006;Tomaz, Schuch, Peil, & Timm, 2014), orange (Guilherme, Marinho, Biazatt, Campos, & Bremenkamp, 2014), pear (Baciu, Achim, & Cosmulescu, 2008), apple (Marcon Filho, Rufato, Rufato, Kretzschmar, & Zancan, 2009;Vaio, Cirillo, Buccheri, & Limongelli, 2009), cherry (Magyar & Hrotkó, 2008), and mango (Posada & Guzmán, 2009). Theoretically, rootstocks may indirectly affect fruit quality by several mechanisms, including budburst, time and abundance of scion flowering and flower quality (Daza, Galavis, Grande, & Santamaria, 2008).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This technique aims to reduce the vigor of plants, increase yield efficiency, and improve fruit quality. These effects have already been verified in several fruit species, such as peach (Rufato et al, 2006;Scarpare Filho et al, 2000;Telles, Biasi, Mindello Neto, & Peters, 2006;Tomaz, Schuch, Peil, & Timm, 2014), orange (Guilherme, Marinho, Biazatt, Campos, & Bremenkamp, 2014), pear (Baciu, Achim, & Cosmulescu, 2008), apple (Marcon Filho, Rufato, Rufato, Kretzschmar, & Zancan, 2009;Vaio, Cirillo, Buccheri, & Limongelli, 2009), cherry (Magyar & Hrotkó, 2008), and mango (Posada & Guzmán, 2009). Theoretically, rootstocks may indirectly affect fruit quality by several mechanisms, including budburst, time and abundance of scion flowering and flower quality (Daza, Galavis, Grande, & Santamaria, 2008).…”
Section: Introductionmentioning
confidence: 79%
“…Scarpare Filho et al (2000) reported that the use of Januária plum interstock anticipated flowering and sprouting of the peach cultivars Tropical and Ouromel-2, enabling early harvesting and showing that each cultivar or species behaves differently. Telles et al (2006) observed that using Irati and Reubennel plums as interstock in the production of peach seedlings proved to be compatible and reduced crown growth.…”
Section: Introductionmentioning
confidence: 99%
“…A falta de influência dos porta-enxertos nessa variável resposta pode ser explicada por tratar de materiais oriundos de pé-franco (Prunus persica (L.) Batsch), tendo de maneira geral seedlings de pessegueiro apresentado boa compatibilidade de enxertia com os cultivares copa produzidos no Brasil. Segundo Telles et al (2006), genótipos com similaridade genética e morfológica desenvolvem proliferação de células meristemáticas e parenquimáticas com afinidades para a formação de um novo sistema vascular, motivo que leva ao sucesso da enxertia. Porém, o sistema de cultivo em campo proporcionou maior porcentagem de enxertos brotados (Tabela 2).…”
Section: R30unclassified
“…No entanto, poucos resultados satisfatórios têm sido alcançados. Telles et al (2006) observaram que o uso de ameixeiras 'Irati' e 'Reubennel' como filtro, na produção de mudas de pessegueiro, mostrou-se compatível e induziu a redução do crescimento das copas.…”
Section: Introductionunclassified